2014
DOI: 10.1089/scd.2013.0563
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TROY Promotes OPC Differentiation and Increases Therapeutic Efficacy of OPC Graft for Spinal Cord Injury

Abstract: Endogenous or graft-derived oligodendrocytes promote myelination and aid in the recovery from central nervous system (CNS) injury. Regulatory mechanisms underlying neural myelination and remyelination in response to injury, including spinal cord injury (SCI), are unclear. In the present study, we demonstrated that TROY serves as an important negative regulator of oligodendrocyte development and that TROY inhibition augments the repair potential of oligodendrocyte precursor cell (OPC) graft for SCI. TROY expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Moreover, the knockdown of Troy in situ transplantation of OPCs leads to notable demyelination and neurological recovery in rats with SCI. [34] Based on the described results, all of the NgR, LINGO-1, PTEN, and Troy are assured being involved in the axon injury during SCI which might interact with each other when neurons were damaged. In our study, we constructed a siRNA pool with results indicating that the expressions of axonal growth inhibitors were reduced remarkably with an increase of cell proliferation and alleviation of the Rho expression in primary spinal cord forms of SCI rats, thereby identifying a promising target mechanism of SCI by modifying the amount of axonal growth inhibitor.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, the knockdown of Troy in situ transplantation of OPCs leads to notable demyelination and neurological recovery in rats with SCI. [34] Based on the described results, all of the NgR, LINGO-1, PTEN, and Troy are assured being involved in the axon injury during SCI which might interact with each other when neurons were damaged. In our study, we constructed a siRNA pool with results indicating that the expressions of axonal growth inhibitors were reduced remarkably with an increase of cell proliferation and alleviation of the Rho expression in primary spinal cord forms of SCI rats, thereby identifying a promising target mechanism of SCI by modifying the amount of axonal growth inhibitor.…”
Section: Discussionmentioning
confidence: 80%
“…Bambakidis and Miller (2004) indicated that transplantation modestly improved functional recovery and spared white matter, but addition of recombinant sonic hedgehog (Shh) during cell transplantation failed to improve either outcome over OPC transplant alone. Knockdown of the TNF receptor TROY increased exogenous remyelination of grafted OPCs as well as hindlimb functional recovery post-injury (Sun et al, 2014). Cao et al (2010) confirmed the ensheathment and remyelination of grafted OPC-derived oligodendrocytes by immuno-EM and were able to correlate improvements in hindlimb function with improvements in oligodendrocyte remyelination by CNTF-expressing OPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was performed as described previously [ 21 , 22 ]. Briefly, cell samples were lysed in a buffer containing 10 mM Tris (pH 7.4), 100 mM NaCl, 1 mM EDTA, 1 mM EGTA, 1 mM NaF, 20 mM Na 4 P 2 O 7 , 2 mM Na 3 VO 4 , 0.1% SDS, 0.5% sodium deoxcholate, 1% Triton-X 100, 10% glycerol, 1 mM PMSF, 60 mg/mL aprotinin, 10 mg/mL leupeptin, and 1 mg/mL pepstatin.…”
Section: Methodsmentioning
confidence: 99%